Erratum: Zhu et al. (2020). Application of the Kano Model and DEMATEL Technique to Explore Sustainable Promotion Strategies for Thai-Chinese Temples as Tourist Attractions. Religions 11: 199 - Bo-Wei Zhu; Zheng Huang; Lei Xiong (Religions, 2021)
The authors would like to make the following corrections about the published paper [...]